Abdominal Ultrasound and Its Diagnostic Accuracy in Diagnosing Acute Appendicitis: A Meta-Analysis - Fu, Jian; Zhou, Xu; Chen, Liang; Lu, Sheng (Frontiers in Surgery, 2021)
Background: Acute appendicitis (AA) is a common cause for abdominal pain encountering unnecessary surgeries in emergency departments. The present meta-analysis aims to assess the accuracy of abdominal ultrasound in suspected acute appendicitis cases in terms of sensitivity, specificity, and post-test odds for positive and negative results. Materials and Methods: An extensive and systematic search was conducted in Medline (via PubMed), Cinahl (via Ebsco), Scopus, and Web of Sciences from 2010 till the end of March 2021. Two authors analyzed studies for inclusion, collected results, and conducted analyses separately. The histopathological study on tissue collected during appendectomy served as the gold standard for determining the final diagnosis. The accuracy was determined by evaluating sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), diagnostic odds ratio. Results: Out of 3193 references, a total of 18 studies were selected. Overall sensitivity of 77.2% (95 % CI – 75.4 – 78.9%) and specificity of 60% (95 % CI – 58% – 62%) were observed. The diagnostic odds ratio of 6.88(95 % CI 1.99 – 23.82) was obtained. Conclusion: Abdominal ultrasound shows significant accuracy of diagnosis in patients with suspected acute appendicitis.